2010
DOI: 10.1111/j.1365-2303.2009.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

EMMPRIN (CD147) expression and differentiation of papillary thyroid carcinoma: implications for immunocytochemistry in FNA cytology

Abstract: These results indicated that EMMPRIN expression correlates significantly with the degree of dedifferentiation of thyroid carcinoma. This study demonstrates the feasibility of expression of EMMPRIN using fine needle aspiration samples. Therefore, immunocytochemical analysis of EMMPRIN may be a novel aid to evaluate the differentiation of thyroid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Previous studies have shown that EMMPRIN/CD147, through multiple pathways and mechanisms, stimulates adjacent fibroblasts to produce matrix metalloproteinases, and thus promotes survival, invasion and metastasis of tumor cells (13,(18)(19)(20)(21)(22)(23)36). Indeed, EMMPRIN/CD147 expression is correlated significantly with the stage of clinicopathology in thyroid carcinoma (9), adenocarcinomas (7), esophageal squamous cell carcinomas (37) and prostate cancer (14). Furthermore, treatment with anti-EMMPRIN/CD147 antibody delays the formation of tumors in animal models (38).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that EMMPRIN/CD147, through multiple pathways and mechanisms, stimulates adjacent fibroblasts to produce matrix metalloproteinases, and thus promotes survival, invasion and metastasis of tumor cells (13,(18)(19)(20)(21)(22)(23)36). Indeed, EMMPRIN/CD147 expression is correlated significantly with the stage of clinicopathology in thyroid carcinoma (9), adenocarcinomas (7), esophageal squamous cell carcinomas (37) and prostate cancer (14). Furthermore, treatment with anti-EMMPRIN/CD147 antibody delays the formation of tumors in animal models (38).…”
Section: Discussionmentioning
confidence: 98%
“…Extracellular matrix metalloproteinase inducer (EMMPRIN, also known as CD147, EMMPRIN/CD147) is a highly glycosylated transmembrane protein and is abundantly expressed on the membrane surface of various tumor cells, including non-small cell lung cancer (NSCLC) (7), macrophage-like lymphoid neoplasm P388D1 cells (8), thyroid carcinoma (9), primary cutaneous malignant melanoma (10), intrahepatic cholangiocarcinoma (11), colorectal/gastric cancer (12), renal cell carcinoma (13), prostate cancer (14), cervical cancer (15), epithelial ovarian cancer (16) and breast carcinoma (17). EMMPRIN/CD147 promotes survival, invasion and metastasis of tumor cells through multiple pathways and mechanisms, including the functional loss of p53, a tumor suppressor (18), upregulated expression of vascular endothelial growth factor (VEGF) (13,(19)(20)(21), disruption of transforming growth factor-β1 (TGF-β1), a growth-modulating factor (22), and regulation of the urokinase-type plasminogen activation (uPA) system of serine proteases (23).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the sample sizes of these studies were small, and the methods were limited to IHC. Aratake et al [16,45] indicated that BSG expression correlates significantly with the degree of dedifferentiation of TC based on immunocytochemical analysis. More interestingly, they also observed MMP-2 positive expression in tumor cells and/or the adjacent tissue in all anaplastic carcinoma (ATC) cases, and the cytological atypia of cells with BSG positive expression was greater than in cells with negative BSG expression.…”
Section: Discussionmentioning
confidence: 99%
“…As for TC, BSG also plays an important role in the tumorigenicity, invasion, metastasis, and degree of dedifferentiation [16,17]. Recently, researchers have identi ed that BSG expression regulates tumor cell glycolysis, resulting in the progression of TC [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…As for TC, BSG also plays an important role in the tumorigenicity, invasion, metastasis, and degree of dedifferentiation [15,16]. Recently, researchers have identified that BSG expression regulates tumor cell glycolysis, resulting in the progression of TC [16,17].…”
Section: Introductionmentioning
confidence: 99%